0,6(y-3)-0,5(y-1)=1,5 решение

0,6(y-3)-0,5(y-1)=1,5 решение

  • 0,6(у-3)-0,5(у-1)=1,5 0,6у-1,8-0,5у+0,5=1,5 0,6у-0,5у=1,5-0,5+1,8 0,1у=2,8 у=2,8:0,1 у=28
  • 0,6(у-3)-0,5(у-1)=1.5
    0,6у-1,8-0,5у+0,5=1,5
    0,1у=1,5+1,8-0,5
    0,1у=2,8
    у=2,8:0,1
    у=28:1
    у=28
    Ответ:у=28
    Я думаю, что так.Надеюсь, что помогла:з
  • Понравилась статья? Поделись с друзьями:
    Добавить комментарий

    ;-) :| :x :twisted: :smile: :shock: :sad: :roll: :razz: :oops: :o :mrgreen: :lol: :idea: :grin: :evil: :cry: :cool: :arrow: :???: :?: :!:

    38 + = 44